Deformation Quantization by Moyal Star-Product and Stratonovich Chaos - Léandre, R.; Obame Nguema, Maurice (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
We make a deformation quantization by Moyal star-product on a space of functions endowed with the normalized Wick product and where Stratonovich chaos are well defined.